Inducible nitric oxide synthase (iNOS) expression may predict distant metastasis in human melanoma - Tschugguel, W (Nature Publishing Group, 1999)
Expression of inducible nitric oxide synthase (iNOS) and its cellular localization was investigated in subcutaneous or lymph node metastases of human melanoma. Immunohistochemistry revealed that iNOS expression was limited to melanoma cells. In samples of patients without distant metastases, the number of iNOS+ tumour cells/total tumour cells was 55% ± 17% (n = 12) compared with 9% ± 8% when distant metastases of lung, liver or brain occurred within an observation period of 3 years (n = 10) (P < 0.001). Western blotting confirmed the expression of iNOS protein in select cases. Notably, iNOS is expressed in regional melanoma metastases and its expression is inversely related to the tumour's metastatic potential. Thus, iNOS expression may have predictive value for the development of distant metastases of human melanoma. © 1999 Cancer Research Campaign